Reflection in Teacher Education: It Starts With Me! - Clare Kosnik (Networks: An Online Journal for Teacher Research, 2003)
In the Mid-Town teacher education program at OISE/UT our broad goals for ourselves and our students are inquiry, integration and community. However, student teachers often enter the program believing they will be systematically taught how to teach mathematics, language arts, science, and so on; acquire fool-proof strategies for classroom management; and be given the names of prescribed curriculum textbooks (Britzman, 1986). As Louisa, a student teacher in this study noted, "I thought teacher education would be sitting in front of a lot of instructors, and you don't have anything to say, because you're going to be told everything that you need to know." Broader goals such as reflection, lifelong learning, and community building seem irrelevant for many at this early point in their careers. So, many student teachers are startled to discover the program is not technical and didactic (Darling-Hammond, Wise, and Klein, 1995). During their practicum placements they are overwhelmed by the complexity of the teachingprocess. As the program progresses, many student teachers begin to realize that learning to teach is not a simple endeavour; rather, it is a life-long process that builds on previous experiences, is shaped by individual contexts, and is a personal journey (Ross, 1990).